Implemetation of Employment Services Application System (SAPK) In Updating Civil Servants Data in Indonesia - Fitriya Dwi Anggraini; Muhammad Alkirom Wildan (JPIM (Jurnal Penelitian Ilmu Manajemen), 2022)
This research background is to find out and analyze the impelementation of staffing service application systems in updating civil servants data in Indonesia.The research method used is qualitatively descriptive. The study used two data sources: direct data and additional data. Information is immediately retrieved by conducting an interview. Additional information is taken from literature studies through books, articles, research journals and media. The results of this study show that through staffing service application systems are able to realize accountable, transparent and up-to-date data. MySAPK application is able to provide faster and excellent service.